Validation of the Inventory of Interpersonal Problems (IIP-64): a comparison of Swedish female outpatients with anorexia nervosa or bulimia nervosa and controls. (4th July 2018) - Lindberg, Karolin; Nevonen, Lauri; Gustafsson, Sanna Aila; Nyman-Carlsson, Erika; Norring, Claes
Abstract: Aim: The aim of the study was to explore the psychometric properties of the Inventory of Interpersonal Problems (IIP-64) and to compare levels of interpersonal distress in Swedish female outpatients with anorexia nervosa or bulimia nervosa with age- and gender-matched controls. Methods: Totally, 401 participants were included; anorexia nervosa ( n  = 74), bulimia nervosa ( n  = 85) and controls ( n  = 242). All participants completed the IIP-64. The eating disorder (ED) patients also filled out the Eating Disorder Inventory-2/3 (EDI). Results: Internal consistency of IIP-64 was acceptable to high. Principal component analyses with varimax rotation of the IIP-64 subscales confirmed the circumplex structure with two underlying orthogonal dimensions; affiliation and dominance. Significant correlations between EDI-3 composite scales ineffectiveness and interpersonal problems and IIP-64 were found. ED patients reported higher levels of interpersonal distress than controls on all but one subscale (intrusive/needy). Conclusions: IIP-64 can be considered to have acceptable to good reliability and validity in a Swedish ED sample. IIP-64 can be a useful complement in assessment of interpersonal problems in ED.